Teachers ‘Liking’ Their Work? Exploring The Digital Labor Of Networked Professional Publics - Rensfeldt, Annika; Hillman, Thomas; Selwyn, Neil (AoIR Selected Papers of Internet Research, 2017)
Social media are now an important aspect of the professional lives of school teachers. This paper explores the growing use of organized ‘teacher groups’ and ‘teacher communities’ on social media platforms such as Facebook. While these online communities are usually celebrated as a welcome means of professional learning and support, the paper explores the extent to which teacher Facebook groups might be understood as ‘work’. Drawing on a detailed examination of a Swedish thematic teacher Facebook group of over 13,000 members, the paper first considers aspects of the online community that could be seen as professionally beneficial and/or valuable – particularly in terms of information exchange and identity-work. Yet while perceived as a relatively beneficial and uncontroversial aspect of teachers’ working lives, the research highlights a number of (largely unrecognized) aspects of the Facebook group that did appear to constitute disadvantaging, exploitative and/or disempowering forms of digital labor. In these terms, the findings highlight tensions between what appears to ‘work’ for individual teachers in the short-term and likely longer-term implications that these practices might have for diminished professionalism and expertise of teaching publics.